Forbidden colors - Mishima, Yukio (Knopf, 1968)
Published in the United States during the 1960s but written years earlier, this Mishima trio, while vastly different in plot, all sport the common theme of idealism destroyed by reality. Nearly three decades after his death, Mishima continues to be a compelling novelist.